Análisis del discurso del candidato presidencial del movimiento creo, Guillermo Lasso, en la red social twitter, elecciones 2021 - María Augusta, Bayas Cauritongo (2022)
ABTRACT This research addresses the analysis of discourse within the political scenario and its interactions, which allows us to understand at a higher level the political dimension that unfolds in social networks, taking Twitter as one of them. For this purpose, we start from structuralist theory, taking into account that the political scenarios in which are always present elements with meaning and symbolism which need to be properly understood. This investigation is based on a descriptive methodology taking into account qualitative matrices for an in-depth analysis, using a total of 840 tweets in Guillermo Lasso's account. In summary, Twitter has become a powerful tool in communication that allows to generate clear and immediate messages positioning political campaign, while at the same time persuades the target audience effectively through well-constructed discursive lines. Keywords: Discourse analysis, Twitter, communication, opinion, information. Firmado electrónicamente por: JOSE MANUEL RUIZ CEPEDA Reviewed by: Lic. José M. Ruiz C. English professor. c.c. 180179272